Effects of Monaural versus Binaural Stimulation on P300 Scalp Topography in Elderly Listeners - Downs, C. Renee; Hymel, Murvin R.; Cranford, Jerry L. (Journal of the American Academy of Audiology, 2001)
The P300 event-related potential was recorded from groups of young and elderly listeners in response to monaural and binaural stimulation. An oddball stimulus paradigm was used to record responses from 19 scalp locations. When listening to binaural stimuli, the young group showed midline and central P300 amplitude maxima, whereas the elderly group exhibited maximal responses in the midline and parietal regions. With monaural stimulation, the young group's responses were similar to those obtained with binaural stimulation. The elderly group, however, showed evidence of a greater contralateral hemisphere response to monaural stimulation during the early part of the P300 response. These findings support the possibility that the P300 neural generators may change with age with respect to temporal onset characteristics or their orientation and strength.Abbreviations: EEG = electroencephalographic, GFP = global field power
Keywords: Auditory event-related potentials; auditory evoked potentials; brain map; elderly; P300; scalp topography